2010
DOI: 10.1037/2152-0828.1.s.84
|View full text |Cite
|
Sign up to set email alerts
|

A cognitive approach to child abuse prevention.

Abstract: We would like to express our appreciation to all the community agencies and individuals involved in the Family Program, along with all the home visitors and families who participated in this study. Services provided within the program were funded by the State of California. Our thanks also go to Veronica Barraza, who skillfully managed the data set, and to Deborah Holmes, who provided clinical supervision to home visitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 64 publications
0
32
0
Order By: Relevance
“…For interventions designed to promote authoritative parenting attitudes, the present study suggests that attention to parental executive functions may also be a necessary step to successfully reduce high-control (e.g., authoritarian) parenting attitudes. There is a successful precedence for including emotion and cognitive control components in home-visiting programs designed to improve parenting (i.e., see Bugental et al, 2002), which may be a useful guide for program directors on how to most effectively incorporate emotion and cognitive capacities into intervention work. Future additional research that assesses the impact of maternal cognitions in parenting skills education interventions would be valuable to improving intervention quality.…”
Section: Discussionmentioning
confidence: 99%
“…For interventions designed to promote authoritative parenting attitudes, the present study suggests that attention to parental executive functions may also be a necessary step to successfully reduce high-control (e.g., authoritarian) parenting attitudes. There is a successful precedence for including emotion and cognitive control components in home-visiting programs designed to improve parenting (i.e., see Bugental et al, 2002), which may be a useful guide for program directors on how to most effectively incorporate emotion and cognitive capacities into intervention work. Future additional research that assesses the impact of maternal cognitions in parenting skills education interventions would be valuable to improving intervention quality.…”
Section: Discussionmentioning
confidence: 99%
“…Parenting seems to be a more powerful causal factor in child maltreatment than distal factors such as the wider social support context. Promoting healthy behaviors during pregnancy and early parenthood (Brayden et al, 1993), establishing social support networks (Bugental et al, 2002), or screening for developmental delay (Duggan et al, 2007) was not found to be effective in preventing child maltreatment. In contrast, significant effects were found for intervention programs offering parent training, such as Multisystemic Therapy for Child Abuse and Neglect (Swenson et al, 2010) and parent-child interaction therapy (PCIT; Chaffin et al, 2004), although in a more recent meta-analysis of five PCIT studies (Kennedy et al, 2016, see Table 2) the combined effect size of d = .31 was not significant (95% CI -0.00-0.62).…”
Section: Interventions To Prevent or Reduce Child Maltreatment Risksmentioning
confidence: 99%
“…Moreover, programs could be enhanced by adding supplemental services and increasing the intensity of certain services to respond to the specific needs of targeted families. For instance, Bugental et al (2002) demonstrated the promise of using enhanced training in parenting skills to improve outcomes for families participating in an HFA program.…”
Section: Matching Services To Families' Needsmentioning
confidence: 99%